ADAM10-mediated ephrin-B2 shedding promotes myofibroblast activation and organ fibrosis - Lagares, David; Ghassemi-Kakroodi, Parisa; Tremblay, Caroline; Santos, Alba; Probst, Clemens K; Franklin, Alicia; Santos, Daniela M; Grasberger, Paula; Ahluwalia, Neil; Montesi, Sydney B; Shea, Barry S; Black, Katharine E; et al. (Nature medicine, 2017)
TGF-β induces expression of ADAM10, which results in greater shedding of ephrin-B2. This shedding promotes the chemotaxis and activation of myofibroblasts and thus the progression of organ fibrosis. Maladaptive wound healing responses to chronic tissue injury result in organ fibrosis. Fibrosis, which entails excessive extracellular matrix (ECM) deposition and tissue remodeling by activated myofibroblasts, leads to loss of proper tissue architecture and organ function; however, the molecular mediators of myofibroblast activation have yet to be fully identified. Here we identify soluble ephrin-B2 (sEphrin-B2) as a new profibrotic mediator in lung and skin fibrosis. We provide molecular, functional and translational evidence that the ectodomain of membrane-bound ephrin-B2 is shed from fibroblasts into the alveolar airspace after lung injury. Shedding of sEphrin-B2 promotes fibroblast chemotaxis and activation via EphB3 and/or EphB4 receptor signaling. We found that mice lacking ephrin-B2 in fibroblasts are protected from skin and lung fibrosis and that a disintegrin and metalloproteinase 10 (ADAM10) is the major ephrin-B2 sheddase in fibroblasts. ADAM10 expression is increased by transforming growth factor (TGF)-β1, and ADAM10-mediated sEphrin-B2 generation is required for TGF-β1-induced myofibroblast activation. Pharmacological inhibition of ADAM10 reduces sEphrin-B2 levels in bronchoalveolar lavage and prevents lung fibrosis in mice. Consistent with the mouse data, ADAM10–sEphrin-B2 signaling is upregulated in fibroblasts from human subjects with idiopathic pulmonary fibrosis. These results uncover a new molecular mechanism of tissue fibrogenesis and identify sEphrin-B2, its receptors EphB3 and EphB4 and ADAM10 as potential therapeutic targets in the treatment of fibrotic diseases.